Decoding Brand Success: The Impact of Identity on Image, Trust, and Loyalty - Rizki, Fitto; Tuti, Meylani (Jurnal Dinamika Manajemen, 2025)
This study aims to analyze the effect of brand identity on brand image, brand trust, brand satisfaction, and brand loyalty. The sampling technique used was accidental sampling to collect data through a survey of 225 respondents who use Evolene in Bogor. The results of the analysis show that brand identity has a significant influence on brand image, with customers who recognize the brand strongly tending to build positive perceptions of the brand. In addition, brand identity has also been shown to influence brand trust, where customer trust in the brandincreases along with the brand’s consistency in delivering its promises and values. The relationship between brand identity and brand satisfaction shows that customer satisfaction can be obtained through experiences that are under the expected brand identity. This study found that brand loyalty is directly influenced by brand identity, with customers who feel connected to the brand more likely to show long-term loyalty. This study provides a theoretical contribution by emphasizing the importance of brand identity management as a basis for forming brandrelationships with customers. Practical implications include developing consistent brand communication strategies, aligning brand values with customer needs, and investing in customer experiences that align with brand identity.